2019
DOI: 10.1007/s13300-019-00683-2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis and Cost-Effectiveness Analysis of Insulin Glargine 100 U/mL Versus Insulin Degludec for the Treatment of Type 2 Diabetes in China

Abstract: IntroductionTo evaluate the efficacy and safety as well as the long-term cost-effectiveness of insulin glargine 100 U/mL (IGlar) versus insulin degludec (IDeg) for the treatment of type 2 diabetes mellitus (T2DM) from the Chinese healthcare system perspective.MethodsA systematic search of English and Chinese electronic databases for randomized controlled trials (RCTs) comparing IGlar with IDeg for the treatment of T2DM was performed, followed by a meta-analysis to compare the efficacy and safety of IGlar versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Global sales of insulin detemir were US$2.7 billion in 2015 and growing at 7.5% per year (38), with global sales of insulin degludec rising 1.8 fold to US$1.11 billion in 2017 versus 2016 (39). Growing sales of insulin detemir and degludec are enhanced by studies suggesting improved cost-effectiveness versus insulin glargine; however, this is not always the case (40)(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…Global sales of insulin detemir were US$2.7 billion in 2015 and growing at 7.5% per year (38), with global sales of insulin degludec rising 1.8 fold to US$1.11 billion in 2017 versus 2016 (39). Growing sales of insulin detemir and degludec are enhanced by studies suggesting improved cost-effectiveness versus insulin glargine; however, this is not always the case (40)(41)(42)(43)(44).…”
mentioning
confidence: 99%
“…[14] There are conflicting results in earlier studies like a meta-analysis by Su W et al, found Glargine was to be superior to degludec. [15] Contrary to this, meta-analysis by Zhou W et al, found degludec much better than glargine. [16] In view of the conflicting data regarding efficacy, it is necessary to compare and prioritize the treatment so far as long-acting insulin use is concerned.…”
Section: Introductionmentioning
confidence: 97%
“… 7 U-100 glargine, the first long-acting insulin analog approved in China, reduces the risk of symptomatic and nocturnal hypoglycemia to a greater extent than NPH insulin in real-life studies from our country. 6 , 8 Glargine has been widely used in China for treatment of T2DM, with cost-saving advantage 9 and acceptable side-effects, such as slight weight gain and low hypoglycemia risk. 9 , 10 However, several critical barriers to BI therapy pose a challenge, including suboptimal dose titration and fear of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Glargine has been widely used in China for treatment of T2DM, with cost-saving advantage 9 and acceptable side-effects, such as slight weight gain and low hypoglycemia risk. 9,10 However, several critical barriers to BI therapy pose a challenge, including suboptimal dose titration and fear of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%